Gold nanoparticles as carriers for a synthetic Streptococcus pneumoniae type 14 conjugate vaccine. (May 2012) - Safari, Dodi; Marradi, Marco; Chiodo, Fabrizio; Th Dekker, Huberta A; Shan, Yulong; Adamo, Roberto; Oscarson, Stefan; Rijkers, Ger T; Lahmann, Martina; Kamerling, Johannis P; Penadés, Soledad; Snippe, Harm
Aims: Coupling of capsular polysaccharides of pathogens to immunogenic protein carriers (conjugate vaccines) improves carbohydrate immune response. Our idea is to explore gold nanoclusters as carriers to prepare fully synthetic carbohydrate vaccines.Materials & methods: Gold glyconanoparticles bearing a synthetic tetrasaccharide epitope related to the Streptococcus pneumoniae type 14 capsular polysaccharide (Pn14PS), the T-helper ovalbumin 323–339 peptide (OVA323–339 ), andD -glucose were prepared by a one-pot method. Their immunogenicity was tested in mice. Cytokine levels after spleen cell stimulation with OVA323–339 were analyzed using a luminex-multiplex cytokine assay. The capacity of the evoked antibodies to promote the uptake of S. pneumoniae type 14 by leukocytes was assessed.Results & discussion: Glyconanoparticles containing 45% of tetrasaccharide and 5% OVA323–339 triggered specific anti-Pn14PS IgG antibodies. Cytokine levels confirmed that glyconanoparticles led to T-helper cell activation. The anti-saccharide antibodies promoted the phagocytosis of type 14 bacteria by human leukocytes, indicating the functionality of the antibodies.Conclusion: Gold nanoparticles have great potential as carriers for the development of a great diversity of fully synthetic carbohydrate-based vaccines. Original submitted 17 May 2011; Revised submitted 27 July 2011